Enrichment in Antioxidant Flavonoids of Stamen Extracts from Nymphaea lotus L. Using Ultrasonic-Assisted Extraction and Macroporous Resin Adsorption - Duangjai Tungmunnithum; Samantha Drouet; Atul Kabra; Christophe Hano (MDPI AG, 2020)
Nymphaea lotus L. is the medicinal plant that has long been used for food, cosmetics and traditional medicines in Africa and Asia since ancient times. Its flavonoids and other interesting phytochemical compounds from rhizome, leaf and the whole flowers have been reported in the previous published research. However, stamens, which are essential for reproductive functions, may also represent new alternative sources of potential antioxidant flavonoids, as investigated in this study. The innovative green chemistry methods, i.e., ultrasound-assisted extraction (UAE) as well as a macroporous resin (MPR) purification procedure, were employed in this current research. Using a full factorial design coupled to three-dimensional (3D) surface plot methodology, the influence of three variables, namely aqEtOH concentration (ranging from 50 to 100% (v/v), US frequency (ranging from 0 (no US applied) to 45 kHz), and the extraction duration (ranging from 20 to 60 min), were evaluated. Five MPRs with different surface areas, average pore diameters, matrix types and polarities were also investigated for the purification of total flavonoids. The optimal UAE condition is 90% (v/v) aqEtOH with 34.65 khz ultrasonic frequency and 46 min of extraction duration. Compared with the conventional heat reflux extraction (HRE) method, a significant 1.35-fold increase in total flavonoids content was obtained using optimized UAE conditions (169.64 for HRE vs. 235.45 mg/g dry weight for UAE), causing a 2.80-fold increase when this UAE associated with MPR purification (475.42 mg/g dry weight). In vitro cell free antioxidant activity of N. lotus stamen extracts and in cellulo antioxidant investigation using yeast model showed the same trend, indicating that the best antioxidant flavonoid can be found in UAE coupled with MPR purification. Moreover, in the yeast model, the expression of key antioxidant genes such as SIR2 and SOD2 were expressed at the highest level in yeast cells treated with the extract from UAE together with MPR purification. Consequently, it can be seen that the UAE combined with MPR purification can help enhance the flavonoid antioxidant potential of the stamens extract from this medicinal species.